Industrial traininig report: Services and Staffing Units, Jabatan Pendidikan Melaka / Muhammad Hazim Muhidin - Muhidin, Muhammad Hazim (Bachelor of Information Science (Hons.) Records Management, 2015)
Due to the statement, trainees have involved in internship session and the place of practical is at Jabatan Pendidikan Melaka. Trainees have learned on how to manage records at JPM according on how these types of organization manage their records. In fact of that, trainees were assigned to contribute such things to their organization for these programmed. This is referring to the special project which all of student records management should have their own special project. On the other hands, this type of organization provided a lot of useful task and activities which trainees can learn and adapt. Those experiences would be useful for trainees themselves. Therefore, trainees will learn about on how to manage records, works smart and integrity, and also in building self-esteem. Thus, the valuable memorial experience can be used in future.